Towards Sustainable Peace, Poverty Eradication, and Shared Prosperity - World Bank (Washington, DC, 2014)
The inauguration of a new presidential administration in Colombia for 2014 to 2018 is the occasion for a new set of policy notes, in which the World Bank provides the incoming administration with a selective diagnostic of current challenges. It independently recommends policies that it deems appropriate to the nation's development process. Colombia's recent progress necessarily demands a new focus on more sophisticated solutions to new questions and to intractable old problems. Three development objectives - sustainable peace, poverty eradication, and shared prosperity - seem within realistic reach for the first time in Colombia history. The three development objectives and the proposed policies to achieve them in nine areas are discussed at length. The nine areas targeted are: 1) rural development; 2) urban development; 3) disaster risk management; 4) environmental sustainability; 5) infrastructure; 6) financial markets; 7) innovation; 8) social protection; and 9) subnational governments. In the past decade the Government has made strenuous efforts to reduce violence and increase state presence, and the country is no longer considered high risk for investment. The note uses international evidence to identify three main transitions Colombia society must undergo to build sustainable peace, including security transition, development transition, and political transition. It also analyzes on a granular level Colombia's poverty and inequality trends over the past decade, most notable of which is the decline of the multidimensional poverty rate. While people may escape poverty, they still remain close to the poverty line and are prone to fall back under it if macroeconomic conditions worsen. Thus, major macroeconomic risks are discussed, as are the environmental risks that put the country in a vulnerable state. A close look is also taken at Colombia's long-term economic growth, which is reportedly uneven across productivity gains and largely influenced by labor reallocations. Achievement of the development objectives can be feasibly advanced through a set of policies.